2017
DOI: 10.4314/rj.v4i1.5f
|View full text |Cite
|
Sign up to set email alerts
|

Strategy to improve the burden of gestational diabetes in African women: Rwandan perspective

Abstract: The global prevalence of gestational diabetes (GDM) in pregnant 20-49 year old women has increased to 16.9%, although data from Africa on GDM are scarce, and risk exposure to pregnant women is unknown. Among the 288 pregnant women screened in Rwanda, 8.3% of women with FPG >126 mg/dL (>6.9 mmol/L) had GDM. Age >41 years (45.8% vs. 18.9%; p<0.001), first-family history of T2D (29.2% vs. 3.4%; p<0.001) and gravidity ≥3 pregnancies (79.2% vs. 29.2%; p=0.05) were associated with GDM. Gestational diabetes is a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…Authors of the review examined 14 studies in six African countries, which indicated prevalence rates from 0% to 13.9% [7]. In contrast to our findings, a study conducted in urban Rwanda reported an 8.3% prevalence rate using the WHO 2006 criteria [19]. Several other studies in SSA reported rates of 8.1% [20], and 5.85% [21] in Nigeria, 8.4% in Tanzania [22], and 9% in Ghana [23], which varies according to diagnostic criteria.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Authors of the review examined 14 studies in six African countries, which indicated prevalence rates from 0% to 13.9% [7]. In contrast to our findings, a study conducted in urban Rwanda reported an 8.3% prevalence rate using the WHO 2006 criteria [19]. Several other studies in SSA reported rates of 8.1% [20], and 5.85% [21] in Nigeria, 8.4% in Tanzania [22], and 9% in Ghana [23], which varies according to diagnostic criteria.…”
Section: Discussioncontrasting
confidence: 92%
“…Other studies conducted in Africa include a systematic review [7], four cross-sectional studies [19][20][21][22] and a prospective study [23]. Authors of the review examined 14 studies in six African countries, which indicated prevalence rates from 0% to 13.9% [7].…”
Section: Discussionmentioning
confidence: 99%
“…After applying our inclusion and exclusion criteria, we ended up with 33 eligible articles [2124, 33–61] for inclusion in this systematic review. Of these, 28 papers contributed towards estimation of GDM prevalence [21, 23, 24, 33–38, 40–42, 4655, 5761], 20 towards assessment of risk factors of GDM [2124, 39, 41, 44, 45, 4750, 5255, 57, 58, 60, 61] and 6 towards the evaluation of the impacts of GDM on maternal and offspring outcomes [39, 43, 47, 51, 57, 61].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Cameroon [23, 47] and Ethiopia [22, 38] contributed two studies each. The other 7 countries (Democratic Republic of Congo [46], Djibouti [51], Ghana [53], Kenya [56], Rwanda [55], Uganda [57] and Zimbabwe [60]) contributed one study each.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the incidence of diabetes in pregnancy was 6.6 per 1000 deliveries (0.66%). This finding was lower than the values that were reported in other African countries [11] [12] [13]. A systematic review of six countries in Africa estimated the overall prevalence of GDM to be 5%; however, there is variability due to the availability of screening procedures and diagnostic criteria [14].…”
Section: Discussionmentioning
confidence: 62%